On center field or at the sidelines? – A plea for a multimodal approach between medical schools and medical student communities while integrating international medical students - Astfalk, Timo (GMS J Med Educ, 2018)
An increasing number of medical schools offer support services for international students. Their frequent focus on linguistic and academic support often reflects a rather deficit-oriented perception of international medical students. Therefore, this comment advocates a stronger focus on the integration into the local medical student communities. This happens both against the background of the expected academic benefits and the added value of intercultural learning at medical schools.